The role of attachment classification on disclosure of self and rater-reported adverse childhood experiences in a sample of child welfare professionals. (December 2017) - Hiles Howard, Amanda R.; Razuri, Erin Becker; Copeland, Rachel; Call, Casey; Nunez, Marisa; Cross, David R.
Abstract: Previous work has found that child welfare professionals have both higher self-report prevalence of adverse childhood experiences (ACEs) (Howard et al., 2015) and higher rates of insecure attachment (Howard et al., 2013) than normative samples. Although adult attachment and ACEs are both prolific areas of research in the developmental literature, little is known about how attachment representations may affect an individual's report of attachment-related ACEs. The current study investigated the role of attachment classification on disclosure of adverse childhood experiences on a self-report questionnaire and a semi-structured clinical interview in a sample of 228 child welfare professionals. Participants completed the Adult Attachment Interview (AAI) and ACE Questionnaire. Data revealed significant differences in self-report and rated disclosure of adverse childhood experiences by attachment classification. No significant differences were found for participants classified as secure-autonomous. Participants classified as dismissing reported fewer ACEs in their self-report questionnaire than independent scorers rated in their AAI. Participants classified as preoccupied reported more ACEs in their self-report questionnaire than independent scorers rated in their AAI. These differences raise questions and may be concerning for both the child welfare professionals and the families they serve. Specifically, future research should focus on possible consequences of having an insecure internal working model and ways to facilitate secure status for professionals if attachment classification is impacting their decisions regarding families. The current study provides a first step in investigating such relations. Highlights: Significant differences in self and rater report of ACEs by attachment were found. Dismissing participants reported fewer ACEs in self than rater report in their AAI. Preoccupied participants reported more ACEs in self than rater report in their AAI. Differences raise questions for both the professionals and the families they serve. Future research should focus on consequences of insecure internal working model.